An Evaluation of the Use of Mechanical Plant in Construction: A Case Study of Selected Number of Sites. - Lasabi, Babatunde Tajudeen (Obafemi Awolowo University, 2014)
The study focuses on the practice of managing construction plants as a pre-condition for their affective utilization in the Nigerian construction industry. It shows that the economic life of a plant depends on adequate maintenance and that appropriate education and training for the plant operators enhances the efficiency of plants and equipments. It also discusses the issue of costing in relation to construction operations and hence highlights the consequences of inadequate computation of costing items.